1979
DOI: 10.1007/bf00501392
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of coronary collateral blood flow on regional vascular resistances

Abstract: A method was applied in anesthetized dogs enabling the measurement of regional resistances up to and behind the start of collaterals and the collateral resistance. The studies show that peripheral coronary pressure, i.e. perfusion pressure of the collaterals, can change when the ratio of pre- and post-collateral resistance alters. Drugs can influence collateral blood flow not only by directly effecting the collaterals but also by altering collateral perfusion pressure. Glyceryl trinitrate given in minor doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Temperature (37°C) and pressure at this blood reservoir were maintained as described earlier [17]. The animals were anesthetized with thiobutabarbital (10 mg/kg), alpha-chloralose (40 mg/kg), and urethane (250 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Temperature (37°C) and pressure at this blood reservoir were maintained as described earlier [17]. The animals were anesthetized with thiobutabarbital (10 mg/kg), alpha-chloralose (40 mg/kg), and urethane (250 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Recent reports (5,21,28,32) pointed out that collateral flow and its early changes after coronary occlusion are mainly determined by the size and number of preexisting coronary collaterals, the size of the area at risk, the perfusion pressure and the extravascular resistance. In accordance, we found that in the animals with collateral state 0-III (group 3), flow was initially low and changed only slightly, whereas it was clearly higher and increased Basic Research in Cardiology, Vol.…”
Section: Mechanisms Governing the Development Of Coronary Collateral mentioning
confidence: 99%